Intrinsic and Extrinsic Motivation Found in Students’ Written Reflection in Play Performance Course - Veronica Esti Nugrahani (Indonesian Journal of EFL and Linguistics, 2018)
As other courses, motivation plays important role in Play Performance course. That motivation can be from the students themselves or other factors outside themselves. This study aimed to examine intrinsic and extrinsic motivation of students’ learning in Play Performance course in English Language Education Study Program of Sanata Dharma University by analyzing their written reflection. There was one formulated research question: “To what extent is intrinsic and extrinsic motivation found in students’ written reflection in Play Performance course?” In this study, document or content analysis was employed. The researcher analyzed 41 students’ written reflection in Play Performance course to find the intrinsic and extrinsic motivation. The findings showed some types of both intrinsic and extrinsic motivation. For intrinsic motivation, there were 15 statements which expressed motivation of knowledge; 19 statements expressing motivation of accomplishment; and 38 statements expressed motivation of stimulation. Meanwhile, for extrinsic motivation, it was found 9 statements expressed motivation of external regulation; 1 statement expressed motivation of introjected regulation; and 2 statements of identified regulation.